#### Answer

$y=\dfrac{C-Ax}{B}$

#### Work Step by Step

Using the properties of equality, in terms of $
y
$, the given expression, $
Ax+By=C
$, is equivalent to
\begin{array}{l}
By=C-Ax
\\\\
y=\dfrac{C-Ax}{B}
.\end{array}

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$y=\dfrac{C-Ax}{B}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.